Potential Vitamin D3 in Reducing Hyperglicemia on Wistar Diabetic Mellitus - Maulidi, Ahmad; Parmasari, Wahyuni Dyah; Ari Tania, Putu Oky; Setiawan, Heru; Sunaryati, Titiek (Fakultas Kedokteran Universitas Brawijaya, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or insulin resistance. Potential alternative to DM management is vitamin D supplementation, which is known to play a role in glucose homeostasis by enhancing insulin sensitivity and protecting pancreatic beta cells. This study aimed to evaluate the effect of vitamin D3 administration on blood glucose levels in Wistar rats induced diabetes mellitus using alloxan. Alloxan causes diabetes by damaging pancreatic β-cells in the islets of Langerhans. This substance enters the cells via the glucose transporter (GLUT2), producing free radicals (ROS), promote oxidative stress and β-cell necrosis, resulting in decreased insulin secretion and increased blood glucose levels. This study uses an experimental design with pre-test and post-test control group. The results showed a significant difference in blood glucose levels between groups (p=0.002) with Kruskal-Wallis Test. The treatment groups (P1 and P2) demonstrated a reduction in blood glucose levels compared to the positive control, with a greater decrease observed in group with the high dose of Vitamin D3, although the difference of glucose level between P1 and P2 was not statistically significant. These findings suggest that vitamin D3 administration plays a beneficial role in lowering blood glucose levels in alloxan-induced diabetic Wistar rats. It may help improve glucose regulation by enhancing insulin sensitivity or protecting pancreatic β-cells from oxidative damage. This paper describes our experimental approach, from the methodology through to the results and discussion, to explore the impact of Vitamin D3 on diabetic Wistar rats.